Molecular and Cellular Studies Reveal Folding Defects of Human Ornithine Aminotransferase Variants Associated With Gyrate Atrophy of the Choroid and Retina - Montioli, Riccardo; Sgaravizzi, Giada; Desbats, Maria Andrea; Grottelli, Silvia; Voltattorni, Carla Borri; Salviati, Leonardo; Cellini, Barbara (Frontiers in Molecular Biosciences, 2021)
The deficit of human ornithine aminotransferase (hOAT) is responsible for gyrate atrophy (GA), a rare recessive inherited disorder. Although more than 60 disease-associated mutations have been identified to date, the molecular mechanisms explaining how each mutation leads to the deficit of OAT are mostly unknown. To fill this gap, we considered six representative missense mutations present in homozygous patients concerning residues spread over the hOAT structure. E. coli expression, spectroscopic, kinetic and bioinformatic analyses, reveal that the R154L and G237D mutations induce a catalytic more than a folding defect, the Q90E and R271K mutations mainly impact folding efficiency, while the E318K and C394Y mutations give rise to both folding and catalytic defects. In a human cellular model of disease folding-defective variants, although at a different extent, display reduced protein levels and/or specific activity, due to increased aggregation and/or degradation propensity. The supplementation with Vitamin B6, to mimic a treatment strategy available for GA patients, does not significantly improve the expression/activity of folding-defective variants, in contrast with the clinical responsiveness of patients bearing the E318K mutation. Thus, we speculate that the action of vitamin B6 could be also independent of hOAT. Overall, these data represent a further effort toward a comprehensive analysis of GA pathogenesis at molecular and cellular level, with important relapses for the improvement of genotype/phenotype correlations and the development of novel treatments.